Succession patterns of fungi associated to wound-induced agarwood in wild Aquilaria malaccensis revealed from quantitative PCR assay - Mohamed, Rozi; Phai, Lee Jong; Ismail, Nurul Irdayu (Springer Netherlands, 2014)
Aquilaria malaccensis produces agarwood in response to wounding and fungal attack. However, information is limited regarding Aquilaria‘s interaction with its diverse fungal community. In this study, time-related changes of three natural fungal colonizers in two wounded wild A. malaccensis were tracked, beginning a few hours after wounding up to 12 months. Using species-specific primers derived from their nrITS sequences in quantitative real-time PCR (qPCR), we quantified the amount of Cunninghamella bainieri, Fusarium solani and Lasiodiplodia theobromae. Because time is a major factor affecting agarwood quantity and quality, 14 wood samples were collected at different time points, i.e., 0–18 h, 2–13 days, 2–18 weeks, and 6–12 months after wounding. qPCR data revealed that the abundance of the three species decreased over time. The fungi were detected in high numbers during the first few hours and days after wounding (40- to 25,000-fold higher levels compared with initial counts) and in low numbers (<1- to 3,200-fold higher than initially) many months later. Consistent with its role in defense response, the accumulation of secondary metabolites at the wounding site could have caused the decline in fungal abundance. Succession patterns of the two trees were not identical, indicating that fungal populations may have been affected by tree environment and wound microclimate. Our results are important for understanding the diversity of microbial community in wild Aquilaria species and their association to wound-induced agarwood formation. Fungi could be secondary triggers to agarwood production in situations where trees are wounded in attempt to induce agarwood.